Users’ perspectives of library space: An analysis of user satisfaction survey at the University of Malaya, Malaysia - Sinnasamy, J.; Saravanan Ramu, N. (2014)
The new millennium with rapid advancement of information and communications technology globally and the appearance of the post millennial net generation library users have created a demanding and competitive environment for academic libraries. On one hand, libraries are competing with virtual google-driven information arena while trying hard to attract users to physically visit the library. Academic libraries are moving towards electronic collection to match the needs of the Net generation. Activities, facilities, and services offered are also revamped as significant library measures to remain relevant. One of the interesting observation of the young library users are their multitasking abilities and their need for a more relaxed atmosphere in contrary to the serious, scholarly milieu of academic libraries in the past. This paper summarizes the open comments on space by library users while answering the User Satisfaction Survey at the University of Malaya, Malaysia. From the open comments, the users’ perspectives of library space can be categorized into five areas; library as a place via extended opening hours, increase in the number of plug points and sockets, high speed wireless and internet services, the need for food and café for relaxation, and aesthetic value and comfort while in the library. Although the University of Malaya library had been taking actions within financial constraints and policy restrictions, to meet the users’ needs, the comments and suggestions over the years nonetheless continue to be along the same lines of the categories mentioned. It can be concluded that the users’ perspectives of the academic library is moving away from the scholarly view to that of library as a third place perhaps due to the availability of electronic books, journals, databases, and resources online.